Evaluation of the quality of educational services at the Islamic Guidance Institute in Indonesia from the point of view of students - Amrullah, AbdulMalik Karim; Bakhabazy, Yaser Salfh Mahfoudh (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the evaluation of the quality of services provided by the Islamic Guidance Institute in Indonesia from the students' point of view, which is represented in: Achieving the objectives of the study followed the descriptive analytical approach. It consists of (20) paragraphs distributed on five axes: the quality of tangible material aspects, the quality of the credibility of the institute and those working with students, the quality of the speed of response of workers to serve students, and the quality of providing safety Attention, respect and passion, and the results of the study showed that the degree of evaluation of educational services provided by the Guidance Institute for students was moderate, as well as the level of evaluation of the quality of educational services at the Islamic Guidance Institute in Indonesia in terms of the institute’s credibility and those working with students was medium.One of the most important findings of the study is that there must be follow-up by the administration of the institute and its officials, periodically and continuously, to provide the services that the student needs, especially the material ones, such as: laboratories, halls, devices, furniture, and libraries, with the need to work to provide Cultural, scientific and sports activities and all the equipment and tools that are needed to carry them out to provide a suitable atmosphere for education.
Keywords: Calendar; Educational Services; Islamic Guidance Institute